The Effect of Descendants of the Prophet in Zabareh on the Development of Shi’ism in Neishaboor in the 4th Century After Hijrah - Mohammad Navidfar; Leila Najafiyan Razavi; Mahmood Mahdavi Damghani (تاریخ اسلام)
Neishaboor considered as one of the centers of Sunnism and the interaction of thoughts and intellectual-religious tendencies in the early Islamic centuries gradually turned towards Shi’ism. The activities of Descendants of the Prophet in Zabareh in the fourth century on the development and stabilization of the Shiite’s position in this city is investigated in the present article. Through the descriptive-analytical method and the study of historical documents, this article concluded that the prepared ground in Neidshaboor, the particular policies of this dynasty, their cultural-religious activities from the entrance to this city to the end of the 4th century as well as their position led to the gradual change in the status of Shiites and changing Neishaboor into one of the religious active centers.